"I Think I'm Reaching My Potential": Students' Self-Determination Experiences in an Inclusive High School. (August 2015) - Eisenman, Laura T.; Pell, Megan M.; Poudel, Bishwa B.; Pleet-Odle, Amy M.
Through a 5-year qualitative case study of an inclusive high school, we examined students' experiences of self-determination. We conducted analyses of multiple interviews with students, parents, teachers, guidance staff, and administrators using grounded theory methods and guided by self-determination conceptual frameworks. Explicit expectations for student agency, a network of caring autonomy-supportive adults, and integrated academic supports emerged as primary features of the students' school experiences. We describe the participants' perspectives about the school structures that supported those experiences and highlight three students who represented a range of responses to the school's model of inclusive learning supports. Implications for fostering self-determination of adolescents with disabilities within general education school settings are considered.